Philippine industry yearbook of labor statistics, 1996. (Manila Department of Labor and Employment, Bureau of Labor and Employment Statistics, 1996)
Purpose: It "presents industry-specific information useful to planners both in government and in the private sector. Offers vital information on industry performance upon which investment priority decisions are shaped."
Contents: Economic and industry performance. Employment and wage statistics. Labor productivity. Labor standard. Occupational injuries. Unionism and collective bargaining. Investment and financial statistics. Directory of DOLE officials and BLES staffs.
Title from cover.
Keywords: Labor supply -- Philippines -- Statistics